Optimization and Evaluation of Piperine Loaded Herbosomes for their Antioxidant and Hepatoprotective Potential - Joshi, Gayatri; Tiwari, Abhishek; Upadhyay, Prashant (Asian Journal of Chemistry, 2022)
Piperine is classified as a class II drug in the biopharmaceutical classification system due to its low aqueous solubility. As a result, piperine herbosomes were created to improve the dissolution rate and in vivo liver protecting activity of piperine and physico-chemical characteristics were used to confirm herbosome formation. The piperine-herbosome formulation revealed spherical particle size of all formulations from P1-P10 and found142.4 ± 0.98 nm for best piperine-herbosome formulation (P2) and a PDI value of 0.237, indicating a homogeneous population of piperine loaded vesicles. In vitro drug release rate and percent entrapment efficiency were determined for all formulations P1-P25 and found to be 95.306 ± 0.21 and 97.306 ± 0.65 in 12 h, respectively for best piperine-herbosome formulation (P2). It exemplifies the complex’s long-term releasing capability. This information suggests that it may have a longer retention time inside the body, extending the duration of effect. The antioxidant potential of pure piperine was determined using the DPPH scavenging method, with an IC50 value of 107.59 ± 0.11 g/mL compared to a formulation with an IC50 value of 93.926 ± 0.03 g/mL. Swiss albino mice of either sex were utilized for the evaluation of hepatoprotective activity. On the 8th day, the hepatotoxicity was caused by giving a single oral dosage of CCl4 (0.5 mL) and the parameters were evaluated on the 9th day. This formulation has the best optimized based on drug content and drug entrapment. Serum glutamic oxaloacetic transaminase (SGOT), serum glutamic-pyruvic transaminase (SGPT), alkaline phosphatase (ALP) and total bilirubin were among the biochemical markers measured. In comparison to normal control (161 ± 0.31 IU/L, 52.78 ± 0.28 IU/L, 121.12 ± 0.14 IU/L and 0.633 ± 1.44 IU/L) and P2 formulation (163.23 ± 0.49 IU/L, 66.9 ± 0.05 IU/L, 128.3 ± 1.15 IU/L and 0.645 ± 0.67 IU/L respectively).